ROLE OF AUTOMATIC CONTROL SYSTEMS IN IMPROVING THE EFFICIENCY OF THERMAL POWER PLANTS - Nishonbaev , Abdulaziz (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article comprehensively analyzes the improvement of energy efficiency, reliability, and environmental performance in thermal power plants (TPP) through the implementation of automatic control systems. The integration of modern distributed control systems (DCS), SCADA, energy management systems (EMS), predictive diagnostics (AMS), and artificial intelligence-based solutions into technological processes is highlighted. The economic and technical effectiveness of automation is evaluated in detail using the example of digitalization programs implemented in Uzbekistan’s TPPs. The article also examines technical, personnel, and regulatory barriers to automation development and proposes recommendations to overcome them.